Bundesstaat und Europäische Union zwischen Konflikt und Kooperation. Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Rostock vom 4. bis 7. Oktober 2006 Federal State and European Union Between Conflict and Cooperation. Autonomy and Commitment of Law-Makers... Responsibility and Efficiency... Financial Autonomy and Financial Interlinking... Jurisdiction Competition Between National Constitutions Courts, EuGH and EuGMR - Tietje, Christian (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2011)
The volume presents the reports and discussions held at the conference of the "Association of German Constitutional Law Teachers" in Rostock from October, 4th to October 7th, 2006.